A protocol to assess the Knee cartilage thickness in healthy older adults and analyze its correlation with patient-reported outcomes - Dias Tina Thomas; Charu Eapen; Atmananda S. Hegde; Prajwal Prabhudev Mane; Ajit R. Mahale (MethodsX)
Knee osteoarthritis (KOA)is a degenerative joint condition affecting about 240 million people worldwide with rising incidences in India. The progressive nature of the disease leads to pain, reduced mobility, and diminished quality of life. Despite extensive global research, there is a lack of normative data on the cartilage thickness specific to the Indian population, which is crucial to understanding the nature of the disease progression. Thereby this study aims to establish normative cartilage thickness values in healthy Indian adults and correlate these values to the knee injury and osteoarthritis outcome score (KOOS). Using ultrasonography, the cartilage thickness will be measured in 100 healthy individuals. Baseline cartilage values will be linked to the various domains of the KOOS score to evaluate early cartilage degeneration and its impact on function. This research will address the gap in Indian-specific data, including early detection and management of KOA and improving clinical decision-making for better outcomes and quality of life. • Establish normative knee cartilage thickness in healthy Indian population using USG. • Helps identify KOA in early stages through USG-based cartilage thickness evaluation • Enables clinicians to target rehabilitation efforts effectively and potentially improve patients' outcomes and quality of life.